School leaders reflections on their school's engagement in a program to foster health literacy development - Rosie Nash (Elsevier, 2021)
Many health attitudes and behaviors formed during childhood are sustained through to adulthood, therefore childhood is a critical time to develop health literacy. Primary schools provide an ideal environment to equip children with lifelong health skills, understanding and knowledge. Through semi-structured interviews, this study gathered primary school leaders’ reflections on the implementation of a program (HealthLit4Kids) designed to foster health literacy development in their schools. The aim of this study was to determine how school leaders experienced the HealthLit4Kids intervention. The results showed that leaders perceived the program had a positive effect on health literacy knowledge and understanding within the school community, as well as improved health behaviors. School leaders’ statements indicated that key barriers such as parental engagement and an overcrowded curriculum would need to be navigated to ensure successful program sustainability.